Case Study Of Moet Hennessy, Louis Vuitton (LVMH) - Ng, Yee Loong (2005)
The approach of creating the right brand image is known as niche marketing. Stringent selection of the distribution network is another critical area in the luxury goods industry. The retail outlets that carry the product reflect the image of the brands. Therefore, they must be carefully selected and be as exclusive as the brands themselves. Not many players in this industry understand the true nature of luxury items, and LVMH is one of the few who does.